155k views
5 votes
Find f(–2), if f(x) = −3x^2 – 5x + 11

User Smelm
by
5.1k points

1 Answer

3 votes

To solve the exercise, replace x = -2 in the function and operate, like this


\begin{gathered} f\mleft(x\mright)=-3x^2-5x+11 \\ f(-2)=-3(-2)^2-5(-2)+11 \\ f(-2)=-3\cdot4+10+11 \\ f(-2)=-12+10+11 \\ f(-2)=9 \end{gathered}

Therefore, the value of the function is 9 when x = -2.

User Nattyddubbs
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.